2020
DOI: 10.1097/md.0000000000022423
|View full text |Cite
|
Sign up to set email alerts
|

Predicting length of stay in patients admitted to stroke rehabilitation with severe and moderate levels of functional impairments

Abstract: Severe stroke patients are known to be associated with larger rehabilitation length of stay (LOS) but other factors besides severity may be contributing. We aim to identify LOS predictors within a population of mostly severe patients and analyze the impact of socioeconomic situation in functionality at admission. A retrospective observational cohort study was conducted including 172 inpatients admitted to a rehabilitation center between 2007 and 2019. Associations with LOS were examined among 30 pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…As improved MRS, ADLs, IADLs, BBS, and MMSE can all reduce the risk of readmission, a routine plan with a continuous rehabilitation process is needed before discharge. Many factors influence subacute rehabilitation LOS, including stroke severity measured with the National Institute of Health Stroke Scale (NIHSS), ability to perform ADLs, or admission Functional Independence Measure (FIM) score (Garcia-Rudolph et al, 2020). This study showed that in the general hospital setting, CVA patients with higher baseline MRS, lower ADLs/IADLs, poorer FOIS, and MNA had longer LOS in PAC units.…”
Section: Discussionmentioning
confidence: 83%
“…As improved MRS, ADLs, IADLs, BBS, and MMSE can all reduce the risk of readmission, a routine plan with a continuous rehabilitation process is needed before discharge. Many factors influence subacute rehabilitation LOS, including stroke severity measured with the National Institute of Health Stroke Scale (NIHSS), ability to perform ADLs, or admission Functional Independence Measure (FIM) score (Garcia-Rudolph et al, 2020). This study showed that in the general hospital setting, CVA patients with higher baseline MRS, lower ADLs/IADLs, poorer FOIS, and MNA had longer LOS in PAC units.…”
Section: Discussionmentioning
confidence: 83%
“…This is in concordance with current evidence that patients with a prolonged LOS exhibited a 9.3-fold higher risk of unfavorable AIS outcomes at discharge than their non-prolonged LOS counterparts. Patients with a severe disability after AIS usually need to be hospitalized for a more extended period because they may require more treatments and rehabilitation support ( 41 43 ). Although it is challenging to accurately predict LOS because of the multifactorial nature of stroke, its prediction is of paramount clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we observed no difference in LOS between AED-exposed and -unexposed patients, suggesting that poorer functional status in AED-exposed patients was not related to greater initial stroke severity. Although we recognise that other factors besides stroke severity contribute to LOS, including socioeconomic status [ 24 ], LOS remains a reliable predictor of and reasonable proxy for stroke severity [ 19 , 25 ]. As mentioned, stroke location was unknown for this cohort, and it is possible that the higher incidence of cortical infarcts in patients who developed post-stroke epilepsy led to more profound motor deficits and ultimately greater disability in performing ADLs.…”
Section: Discussionmentioning
confidence: 99%